Accumulation of Copper and Lead in Selected Medicinal Plants - Shavakh, S.; Ghalandari Kavkani, S.; Nouri, J. (Asian Journal of Chemistry, 2013)
The present study aims to estimate lead and copper metals content in four medicinal plants collected from different sites of Saveh region located in south western of Tehran, in June and August 2010. Samples of Eucalyptus globules, Mentha piperita, Thymus vulgaris and Rosa damascena were separately collected from different locations and prepared in laboratory. Lead and copper content were measured in each samples using atomic absorption spectrophotometry. Results show that lead content was the highest in Mentha piperita and the lowest was in T. vulgaris. However, T. vulgaris and E. globulus contained the highest and the lowest levels of copper, respectively. Overall, despite of vital advantages of studied medicinal plants, heavy metals contamination prevent of therapeutic uses of these plants which may result in fatal effects on human health.